PLYOMETRY TRAINING IN KARATE- SPECIFICS - Sandra Vujkov (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
Plyometric training is one of the most interesting innovations in the recent few decades in the process of sport training. The experience of coaches and athletes who have practised this kind of training proces brought them to higher performance in sports results. Plyometric exercise is developed and applied in conformity with certain sport requirements. Plyometry is a training method, which should be applied in combination with other methods for strenght development in overall programme of training, all in favour of improvement of the relationship between maximal strenght and explosive strenght, being very important for karate sport. This paper deals with a proposal of a few exercises that should have a positive transfer on improvement of the performance of karate tehnique.